(untitled) - Celce-Murcia, Marianne (Cambridge, UK, 2000)
This book offers current and prospective teachers of English a comprehensive treatment of prounuciation pedagogy, drawing on both current theory and practice.
Ngữ âm thực hành nâng cao,Ngữ âm thực hành cơ bản
Keywords: English language,English language,English language; Pronunciation,Study and teaching,Pronunciation by foreign speakers,Study and teaching